The effect of early-onset preeclampsia on the intestinal blood flow of preterm infants - Pelicia, Simone Manso de Carvalho [UNESP]; Fekete, Saskia Maria Wiegerinck [UNESP]; Corrente, José Eduardo [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP] (Taylor & Francis, 2019)
Background: Preeclampsia is associated with important vascular maternal changes. However, its repercussions on newborns’ circulation have hardly been reported. Objective: To investigate whether early-onset preeclampsia is associated with altered blood flow of the superior mesenteric artery (SMA) in preterm infants. Materials and methods: Prospective study with 60 preterm infants of mothers with early-onset preeclampsia (PE) and 60 of normotensive mothers, paired according to the gestational age, from 2013 to 2016. Maternal, gestational, and neonatal clinical data were evaluated. The outcome of interest was the blood flow velocity in SMA, evaluated by the peak systolic velocity and end-diastolic velocity and by the resistance index and pulsatility index, through the Doppler ultrasound in the first 72 h of life. Covariance analysis was used to determine the PE effect on the SMA blood flow, controlling for possible confounding variables. Results: The mean gestational age was 30 weeks. Infants of mothers with PE had significantly lower values of peak systolic and end-diastolic velocity (57.75 ± 17.49 and 12.29 ± 5.74) compared with the control group (67.17 ± 29.57 and 15.03 ± 7.52), even after control of covariates. Conclusion: Early-onset preeclampsia is associated with decreased blood flow of SMA in preterm infants on the first days of life.
Keywords: Doppler ultrasonography; gastrointestinal tract; preeclampsia; preterm infant